Pengembangan Media Interaktif Pembelajaran Maharah Qiro’ah Platform Website di SMA IT AR RAIHAN Bandar Lampung - Syakur, Farhan (An Naba, 2024)
The innovation of technology-based learning in the form of digital learning media has been extensively developed, including in Arabic language learning. However, environmental observations at SMA IT Ar Raihan Bandar Lampung, X grade, indicate that the existing digital media have not addressed real problems in the school. This research and development of interactive web-based maharah qira’ah learning media aims to facilitate the needs of Arabic language learning activities in the school. The development of this interactive media addresses the teachers' needs to deliver core material to students who have difficulty learning Arabic due to the complexity of the material and student intake. The development of this learning media uses the ADDIE development model. The media developed was validated by media experts, content experts, and learning experts, and was tested on 27 students. The content expert validity test showed very feasible results with an average score of 4.9; the media expert validity test showed very feasible results with an average score of 4.4; and the learning expert validity test showed very feasible results with an average score of 4.6. The researcher developed interactive maharah qira’ah learning media in the form of a website because the students in the school use 1:1 tablet devices that can access material anytime and anywhere, and considering its usefulness for use by other schools.